2004
DOI: 10.1016/j.joca.2004.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A pilot, two-year longitudinal study of the interrelationship between trabecular bone and articular cartilage in the osteoarthritic knee

Abstract: This study quantifies the changes in bone and cartilage structural parameters over time, and demonstrates a longitudinal relationship between the morphological changes in bone and cartilage structure in patients with varying degrees of OA. Although a large variation of bone and cartilage changes is apparent among subjects, significant trends are evident in a relatively small sample size, with a short follow-up duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 39 publications
6
89
0
Order By: Relevance
“…Data also revealed that the loss of cartilage volume/thickness and the deterioration of the subchondral bone structure were interdependent in longitudinal studies in knee OA patients [12,14]. The loss of cartilage, subchondral bone alterations and osteopenia of the underlying trabecular bone were all correlated in some of these patients.…”
Section: Osteoarthritismentioning
confidence: 88%
“…Data also revealed that the loss of cartilage volume/thickness and the deterioration of the subchondral bone structure were interdependent in longitudinal studies in knee OA patients [12,14]. The loss of cartilage, subchondral bone alterations and osteopenia of the underlying trabecular bone were all correlated in some of these patients.…”
Section: Osteoarthritismentioning
confidence: 88%
“…BV/TV, app.Tb.N and app.Tb.Th, and of increasing app.Tb. Sp in the femur, lateral femoral condyle and medial femoral condyle in OA patients during a 2-year longitudinal study [10]. This implies that there might be some relationship between cartilage and trabecular bone in OA patients, thus requiring further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…The measurement of trabecular bone structure with MRI offers a quantitative assessment of OP progression and therapeutic monitoring in patient studies [8]. In addition, the superior SNR of ultra-high-field strengths is expected to improve image quality and to assist in evaluating cross-correlations between cartilage and bone changes during the progression of OA [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…OA has been defined by the American College of Rheumatology (ACR) as a 'heterogeneous group of conditions that leads to joint symptoms and signs which are associated with defective integrity of articular cartilage, in addition to related changes in the underlying bone at the joint margins'. It remains an open question whether the initial changes take place in cartilage or bone or other articular tissues and, more importantly, what the causal relationship between these changes is (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) narrowing; JSW, joint space width; K, knee; KLG, Kellgren Lawrence grade; KOSS, knee osteoarthritis scoring system; LF, lateral femoral condyle; LT, lateral tibia; MRI, magnetic resonance imaging; MF, medial femoral condyle; MT, medial tibia; OA, osteoarthritis; OAI, Osteoarthritis Initiative; P, patella; PGs, proteoglycans; pLF, posterior aspect of the lateral femoral condyle; pMF, posterior aspect of the medial femoral condyle; qMRI, quantitative magnetic resonance imaging; SNR, signalto-noise ratio; SPGR, spoiled gradient echo; SSFP,steady-state free precession; T, tibia; T 1 , longitudinal relaxation time; T 1rho , T 1 in the rotating frame; T 2 , transverse relaxation time; tAB, total area of subchondral bone; ThC, thickness of the cartilage; ThCcAB, thickness of the cartilage, summarized over cAB (without including denuded areas as 0 mm cartilage thickness); ThCtAB, thickness of the cartilage, summarized over tAB (including denuded areas as 0 mm cartilage thickness); TKA, total knee arthroplasty; TrF, trochlear of femur; VC, volume of cartilage; VctAB, volume of cartilage normalized to the total area of subchondral bone (tAB); we, water excitation; WOMAC, Western Ontario McMaster University-Index; WORMS, whole-organ MRI score; mCT, micro-computed tomography.…”
Section: Rationale For Quantitative Mri Of Cartilage and Bone In Ostementioning
confidence: 99%
“…Owing to its lack of radiation and cross-sectional nature, however, high resolution MRI is a more promising tool in assessing bone structure non-invasively, but obtaining images in vivo with a suitable spatial resolution is still challenging. Previous investigations have used 1.5 T scanners combined with surface coils dedicated for high resolution imaging for that purpose (8,13,207) and have studied the knee using high-resolution 3D gradient echo sequences. Axial fast gradient echo sequences were used with an echo (TE) of 4.5 ms, a repetition time (TR) of 30 ms, a flip angle (FA) ¼ 408, a field of view of 10 cm and a matrix size of 512  384 pixels corresponding to a reconstructed spatial resolution of 0.195 mm  0.195 mm.…”
Section: Quantitative Measurement Of Bone Structure In Oa Hardware Anmentioning
confidence: 99%